Potensi Konsorsium Bakteri Pseudomonad fluorescent dan Bacillus mycoides Terhadap Penyakit Layu Bakteri Secara In-vitro - Sagala, Yosua Nathanael Itona; Prasetyawati, Endang Triwahyu; Wuryandari, Yenny (Universitas Andalas, 2024)
Bacterial wilt disease caused by Ralstonia solanacearum is a disease in chili pepper plants (Capsicum annuum) that is difficult to control. One technique to prevent bacterial wilt disease is consortium of antagonistic bacteria such as Pseudomonad fluorescent and Bacillus mycoides. This study aimed to determine whether the consortium of Pseudomonad fluorescent pf-142 and Bacillus mycoides can inhibit R. solanacearum better than a single application in-vitro. This study was conducted in a Completely Randomized Design (CRD) with four treatments (Pseudomonad fluorescent pf-142, B. mycoides, Pseudomonad fluorescent pf-142 + B. mycoides, and control) in six replications, resulting in 24 experimental units. The variables observed were the symptoms of attack and pathogenicity of R. solanacearum, compatibility and inhibitory rate of the consortium of Pseudomonad fluorescens pf-142 and B. mycoides against R. solanacearum. Based on the study, it was known that R. solanacearum caused wilting in chili pepper plants with high virulence. Pseudomonad fluorescent pf-142 and B. mycoides did not produce an inhibition zone, indicating that both were compatible. The consortium of Pseudomonad fluorescent pf-142 and B. mycoides provided the widest inhibition zone, indicating strong antagonistic ability against R. solanacearum.